BRAF(V)(600E) or mutant MAP2K1 human CD34(+) cells establish Langerhans cell–like histiocytosis in immune-deficient mice - Rafiei, Anahita (Blood Adv, 2020)
BRAF(V600E) or mutant MAP2K1 expression in human CB CD34(+) HSPCs lead to Langerhans cell–like histiocytosis in immune-deficient mice. BRAF(V600E)-expressing human CB CD34(+) HSPCs did not generate hairy cell leukemia in xenograft mouse models.